2022
DOI: 10.1186/s13068-022-02212-z
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal photoautotrophic growth induces pH decrease in the aquatic environment by acidic metabolites secretion

Abstract: Background Microalgae can absorb CO2 during photosynthesis, which causes the aquatic environmental pH to rise. However, the pH is reduced when microalga Euglena gracilis (EG) is cultivated under photoautotrophic conditions. The mechanism behind this unique phenomenon is not yet elucidated. Results The present study evaluated the growth of EG, compared to Chlorella vulgaris (CV), as the control group; analyzed the dissolved organic matter (DOM) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The significant surge in TIC levels and the corresponding pH shift in strain MAS3 could be indicative of its more efficient heterotrophic metabolism compared to that in strain MAS1. However, Wu et al 46 observed a decrease in pH upon microalgal photoautotrophic growth in the aquatic environment due to the secretion of acidic metabolites. Other studies also indicated that the TOC-to-TN ratio can influence the nutrient removal process, particularly during microalgal wastewater treatment.…”
Section: Adaptability and Efficiency Of Acid-tolerant Microalgae In H...mentioning
confidence: 99%
“…The significant surge in TIC levels and the corresponding pH shift in strain MAS3 could be indicative of its more efficient heterotrophic metabolism compared to that in strain MAS1. However, Wu et al 46 observed a decrease in pH upon microalgal photoautotrophic growth in the aquatic environment due to the secretion of acidic metabolites. Other studies also indicated that the TOC-to-TN ratio can influence the nutrient removal process, particularly during microalgal wastewater treatment.…”
Section: Adaptability and Efficiency Of Acid-tolerant Microalgae In H...mentioning
confidence: 99%
“…In contrast with the present study, a pH decrease was reported in photobioreactors with other microalgal species described as hyperproducers of humic acids, such as Euglena sp. [38]. The co-production of other acid compounds such as itaconic acid by these microalgae was responsible for the pH decrease in such photobioreactors [39].…”
Section: Physical-chemical Characteristics Of Uww and Conventional Po...mentioning
confidence: 99%
“…acids, such as Euglena sp. [38]. The co-production of other acid compounds such as itaconic acid by these microalgae was responsible for the pH decrease in such photobioreactors [39].…”
Section: Physical-chemical Characteristics Of Uww and Conventional Po...mentioning
confidence: 99%
“…In the majority of bioreactors, light supply, [ 50–52,81 ] cell concentration, [ 82–84 ] CO 2 concentration, [ 85,86 ] pH, [ 87–91 ] temperature, [ 52,92 ] concentration of nutrients, [ 91 ] and other parameters are affected by and have an impact on the growth of microorganisms. [ 89,91,93–95 ] These systems must be monitored and externally maintained to achieve optimal results [ 85,95 ] which adds to the overall cost.…”
Section: Photobioreactor Design Is Pivotal For High Yield Of Microalgaementioning
confidence: 99%